2014
DOI: 10.1016/j.jcin.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Outcomes of Recurrent Stent Thrombosis

Abstract: rST represents an important cause of long-term morbidity and mortality after an initial ST. Bifurcation ST and a larger proximal reference vessel diameter are independently associated with an increased risk of rST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
1
11
0
4
Order By: Relevance
“…Compared with short-term DAPT (3 or 6 months), long-term DAPT (≥12 months) significantly reduced the risk of cardiac ischemic events. 25 For patients with prior stent thrombosis, a study from Armstrong et al 26 showed that patients with an initial stent thrombosis are at high risk for recurrent stent thrombosis; thus, a longer DAPT duration for these patients may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with short-term DAPT (3 or 6 months), long-term DAPT (≥12 months) significantly reduced the risk of cardiac ischemic events. 25 For patients with prior stent thrombosis, a study from Armstrong et al 26 showed that patients with an initial stent thrombosis are at high risk for recurrent stent thrombosis; thus, a longer DAPT duration for these patients may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Armstrong et al reported on a combined retrospective and prospective observational California registry of angiographic definite stent thrombosis at five academic hospitals from 2005 to 2013. 248 The entry criterion was the occurrence of a definite stent thrombosis, which was observed in 221 patients overall out of an unknown number of patients at risk. With the important caveat of not knowing for each stent type the exact timing of the first stent thrombosis event after the index procedure, 104 (47%) patients had received a first generation DES, 51 (23%) a BMS, and 19 (9%) a second generation DES.…”
Section: Dual Antiplatelet Therapy Decision Making In Patients With Smentioning
confidence: 99%
“…Doniesienie naukowe Armstronga i wsp. [248] obejmowało połączone dane retrospektywne i prospektywne z obserwacyjnego rejestru z Kalifornii, który uwzględniał występowanie stwierdzonej angiograficznie zakrzepicy w stencie w 5 szpitalach akademickich w latach 2005-2013. Kryterium włączenia do badania było wystąpienie potwierdzonej zakrzepicy w stencie, którą rozpoznano u 221 pacjentów z nieograniczonej liczebnie grupy chorych obciążonych ryzykiem zakrzepicy.…”
Section: Podejmowanie Decyzji O Podwójnejunclassified